(untitled) (Research, Society and Development, 2022)
The use of medicinal plants is an ancient practice, especially Momordica charantia L., which has several applications, especially with regard to the treatment of skin lesions. Thus, the objective was to survey the literature on the use of Momordica charantia L. in the treatment of skin lesions. This is an integrative review where a search for studies was carried out in the following databases: SciELO, PubMed and VHL, using the DeCS: Momordica charantia, Wounds and Injuries, and Skin “Skin”, being them combined using the Boolean operator “AND. Studies available in full in Portuguese and English were included, which had two of the descriptors, and which covered the time period of ten years. Studies outside the theme, which did not understand the delimited period and in other languages ​​were excluded. The analysis showed that the use of Momordica charantia L. has great potential to be applied to skin lesions in its various pharmaceutical forms. This fact is justified due to its pharmacological properties attributed to the presence of phytochemicals already identified and which have shown efficacy for the treatment of skin lesions. Although there are no studies in the literature developed with human beings, the research carried out in animals showed to be promising, and the most used organ in these were the leaves. Further investigations involving more advanced experimental techniques are still needed, in order to thoroughly elucidate its mechanism of action, pharmacological and toxicological effects, and it can become a drug and expand the range of therapeutic options in the treatment of skin wounds.